Duha Prayer in Improving the Spiritual Intelligence of Grade VIII Students at MTS Miftahul Huda - Fitriana Fitriana; Umar Al Faruq A Hasyim; Irhamudin Irhamudin (CV. Creative Tugu Pena, 2023)
This article aimed to determine the effect of Duha prayer in improving the spiritual intelligence of Grade VIII students at MTs Miftahul Huda Nambah Dadi Village, Terbanggi Besar District Central Lampung Regency. This study used a qualitative method. The subjects was 30 participants. Data collection used documentation and questionnaires. While the technique analyzing data used triangulation. The results showed that Duha prayer is very influential in increasing spiritual intelligence. The process of forming spiritual intelligence in madrasas is in the form of habituating religious activities, educating morals on a spiritual basis (aqidah and faith) which directs students to reach the degree of ihsan. Religious culture in educational institutions is a culture that was created from the habituation of religious activities that lasts a long time and continuously, even to the point where self-awareness emerges from all members of the educational institution to carry out these religious values. To the extent that their hearts are restless if they do not carry out religious activities or violate the religious culture that has become a habit and a spiritual need for humans. Keywords: Improving Spiritual Intelligence, Effect of Duha Prayer, Spiritual Intelligence